Generation of human oogonia from induced pluripotent stem cells in vitro - Yamashiro, Chika; Sasaki, Kotaro; Yabuta, Yukihiro; Kojima, Yoji; Nakamura, Tomonori; Okamoto, Ikuhiro; Yokobayashi, Shihori; Murase, Yusuke; Ishikura, Yukiko; Shirane, Kenjiro; Sasaki, Hiroyuki; Yamamoto, Takuya; et al. (Science (American Association for the Advancement of Science), 2018)
Human in vitro gametogenesis may transform reproductive medicine. Human pluripotent stem cells (hPSCs) have been induced into primordial germ cell-like cells (hPGCLCs); however, further differentiation to a mature germ cell has not been achieved. Here, we show that hPGCLCs differentiate progressively into oogonia-like cells during a long-term in vitro culture (approximately 4 months) in xenogeneic reconstituted ovaries with mouse embryonic ovarian somatic cells. The hPGCLC-derived oogonia display hallmarks of epigenetic reprogramming-genome-wide DNA demethylation, imprint erasure, and extinguishment of aberrant DNA methylation in hPSCs-and acquire an immediate precursory state for meiotic recombination. Furthermore, the inactive X chromosome shows a progressive demethylation and reactivation, albeit partially. These findings establish the germline competence of hPSCs and provide a critical step toward human in vitro gametogenesis.